Promoting Walkability in Streets: Analytical Study of Salem Street, Sulaimani, Iraq - Salam, Daban Abdulla; Yaseen Raof, Binaee; Dhiaadin Bahaadin, Sara (Kurdistan Journal of Applied Research, 2020)
Walking represents a vital transport system for people to maintain balanced and healthy lifestyles and to improve the environmental conditions. Within a contemporary metropolitan society, other means of transport are often preferred. The presented paper aims to examine the methods of how to encourage people to walk. By organizing it into three main sections to begin with, the work of in order to investigate the nature of the metropolitan individual and the contemporary society. The second section builds on the outcomes of the first section. Hence it provides a clear rationale for the adoption of strategies that would encourage people to walk. Salim Street which is one of the important and vibrant streets inside Sulaimani city is being chosen for this study, its possibility to be a walk able street is analyzed. The third section provides practical solutions and steeps on how to promote walking among the contemporary society. then, a brief conclusion summarizes the key arguments encompassed in the presented paper and draws wider implications and recommendations for city planners to build more pedestrian friendly streets.